The discursive construction of Southeast Asia in 19th century colonial-capitalist discourse - Farish A. Noor (Farish Ahmad Noor), 1967- author. Link
1 online resource.
Keywords: The nations of Southeast Asia today are rapidly integrating economically and politically, but that integration is also counterbalanced by forces ranging from hyper-nationalism to disputes over cultural ownership throughout the region. Those forces, Farish A. Noor argues in this book, have their roots in the region's failure to come to a critical understanding of how current national and cultural identities in the region came about. To remedy that, Noor offers a close account of the construction of Southeast Asia in the nineteenth century by the forces of capitalism and imperialism, and shows how that construct remains a potent aspect of political, economic, and cultural disputes today.